Perioperative patient safety recommendations: systematic review of clinical practice guidelines - Martinez-Nicolas, Ismael; Arnal-Velasco, Daniel; Romero-García, Eva; Fabregas, Neus; Sanduende Otero, Yolanda; Leon, Irene; Bartakke, Ashish A; Silva-Garcia, Javier; Rodriguez, Anna; Valli, Claudia; Zamarian, Sandro; Zaludek, Adam; et al. (BJS open, 2024)
BACKGROUND: Surgical-related incidents are a common cause of in-hospital adverse events. Surgical patient safety would benefit from evidence-based practices, but a comprehensive collection of patient safety recommendations is still lacking. This study aimed to compile and assess the perioperative patient safety recommendations for adults. METHOD: A systematic review of clinical practice guidelines was conducted using Medline, Embase, Cochrane, Virtual Health Library Regional Portal, and Trip Database from 2012 to 2022. Eligibility criteria followed a PICAR strategy for patient safety recommendations in the perioperative care continuum. Guidelines were appraised for quality, particularly focusing on the 'rigour of development' domain of the AGREE-II tool for those containing strong recommendations. Descriptive analyses were conducted, emphasizing guideline quality, recommendation strength, and the supporting level of evidence. RESULTS: From the 267 guidelines, 4666 perioperative patient safety recommendations were extracted, of which 44.9% (2095) were strongly recommended. Of these, 322 had the highest level of evidence, but only 18 guidelines met high standards in the AGREE-II 'rigour of development' domain. A subset of 78 recommendations ranked the highest in the strength of recommendation, level of evidence, and rigour of development of their guidelines. A gap was found within pre-admission and post-discharge care recommendations. DISCUSSION: This review highlights the noteworthy variability in the methodological quality of the guidelines, and a discordance between strength of recommendation and evidence level of the available perioperative patient safety recommendations. These findings provide valuable information for advising policy decisions and promoting best practices to enhance global surgical safety. REGISTRATION: PROSPERO (CRD42022347449).
Keywords: směrnice pro lékařskou praxi jako téma; Patient Safety; Perioperative Care; bezpečnost pacientů; Humans; Practice Guidelines as Topic; lidé; perioperační péče